Frequency of thyroid cancer in patients operated at Cantonal Hospital Zenica, Bosnia and Herzegovina, in the period 2007- 2014 - Nermin Hrnčić; Amna Goga; Selma Hrnčić; Marijana Filipovska-Mušanović; Haris Hatibović; Đenad Hodžić (Medicinski glasnik, 2016)
Aim: To determine frequency and type of thyroid cancer (TC) as well as gender and age distribution of patients operated at the Department of Ear, Nose and Throat (ENT), Cantonal Hospital Zenica, Bosnia and Herzegovina. Methods: A retrospective analysis of data obtained from an operating protocol and disease history of patients operated in the eightyear period (2007- 2014) was made according to the frequency and type of thyroid cancer, as well as age and gender of the patients. χ2 test was used for statistical with p˂0.05. Results: A total of 818 surgeries of the thyroid gland were conducted, in 714 (87.29%) female and 104 (12.71%) male patients. Malignancies were diagnosed in 74 (9.05%) patients, of whom 64 (86.49%) were females and 10 (13.51%) were males, resulting in the gender prevalence of 8.96% and 9.62%, respectively. The most often presented type was papillary carcinoma, in 48 (out of 74, 64.86%) patients, followed by follicular carcinoma in 10 (13.51%), medullary carcinoma in four (5.41%), Hurthle cell carcinoma in four (5.41%) patients, while anaplastic carcinoma was found in one (1.35%) patient. The number of diagnosed malignancy varied from 0% (in 2007) to 13.91% (in 2014) (p=0.05). Conclusion: The prevalence of thyroid cancer is low, but has an increasing trend. A large number of unnecessary surgeries on thyroid gland was performed. Preoperative diagnostic procedures for diseases of the thyroid gland in Cantonal Hospital Zenica should be improved in order to avoid unessential surgeries.
Keywords: thyroidectomy; malignant disease; thyroid nodule